Ejector integration for the cost effective design of the Selexol™ process. (1st November 2018) - Ashrafi, Omid; Bashiri, Hamed; Esmaeili, Amin; Sapoundjiev, Hristo; Navarri, Philippe
Abstract: This work introduces a novel approach to reduce the energy demand as well as capital and operating costs in a widely used gas purification process by optimal integration of ejector technology. Three scenarios for ejector integration have been identified into a dual-stage Selexol™ process configuration for H2 S and CO2 removal from syngas. The clean syngas met the requirement to be used in an integrated gasification combined cycle. The intention was to unload or eliminate compressors used in the conventional design, and to reduce the capital and operating costs. Aspen HYSYS ® is used to develop a detailed simulation model of the Selexol™ process and to assess the impacts of the proposed design configurations from an energy and economic perspective. A predictive design model is also used to evaluate the operating conditions of the proposed ejectors. Among the scenarios investigated, it is found that ejector integration is attractive only if one or some compressors can be eliminated. This work shows that an optimally integrated ejector in the CO2 recovery and compression section of the Selexol™ process can reduce the capital costs by up to 28%, while reducing the operating costs by up to 6%. Highlights: A dual-stage Selexol™ acid gas removal process from syngas is simulated. A heat integration analysis is used to optimize the use of energy in the process. Integration of ejector in the process is investigated for a cost-effective design. Several scenarios for ejector integration are identified to eliminate compressors. It is shown that the proposed improvement strategies can reduce the CAPEX and OPEX.